Between Science and Art: Thin Sound Absorbers Inspired by Slavic Ornaments - Krushynska, Anastasiia O. (Frontiers in Materials, 2019)
Acoustic metamaterials have opened promising opportunities for manipulation of low-frequency sound and development of compact structures with a broadband acoustic performance for noise mitigation applications, room, and architectural acoustics. So far, several mechanisms have been studied to achieve broadband sound absorption at subwavelength frequencies, when the system thickness is much smaller than the wavelength of sound waves. In this paper, we analyze two other approaches based on the use of interacting and coupled resonators with the aim to further reduce a structural thickness. We numerically demonstrate that properly designed panels with interacting resonators allow extending a single-peak absorption to broadband frequencies, while coupled resonators enable achieving broadband absorption at several frequency ranges. The developed designs are inspired by ancient Slavic folk patterns, attracting attention by their delicate ligature, multi-layered structure, and concealed meaning. Our results open new possibilities for creating acoustic metamaterials with art effects, which provide meaning to occupied space and make these metamaterials more appealing for applications.